2018
DOI: 10.1183/13993003.00407-2018
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of severe varicella pneumonia with respiratory failure admitted to the intensive care unit for mechanical ventilation

Abstract: The outcome of severe varicella pneumonia with respiratory failure admitted to the intensive care unit for mechanical ventilation To the Editor: Varicella pneumonia carries a mortality of 10-30%; mortality rate increases to 50% in patients that warrant mechanical ventilation secondary to respiratory failure despite appropriate antiviral and supportive treatment. Risk factors for the development of severe disease include cigarette smoking, pregnancy, immunocompromised states and more extensive skin involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Severe pneumonia not only causes severe respiratory symptoms and hypoxia, but also results in the dysfunction of other organs and even multiple organ failure, with a high fatality rate. Respiratory failure is one of the most important causes of mortality in patients with severe pneumonia[ 1 ]. Mechanical ventilation is a common method for the clinical treatment of severe pneumonia complicated by respiratory failure, and it can rapidly improve oxygenation, correct body hypoxia, and improve hypoxia in other organs[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe pneumonia not only causes severe respiratory symptoms and hypoxia, but also results in the dysfunction of other organs and even multiple organ failure, with a high fatality rate. Respiratory failure is one of the most important causes of mortality in patients with severe pneumonia[ 1 ]. Mechanical ventilation is a common method for the clinical treatment of severe pneumonia complicated by respiratory failure, and it can rapidly improve oxygenation, correct body hypoxia, and improve hypoxia in other organs[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous studies have proved that mechanical ventilation has become an important means to treat critically ill patients. 14 Early anti-infection treatment is conducive to shortening the mechanical ventilation time and reducing the mortality. All these findings demonstrated that early sampling could provide patients with greater opportunities for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] There are various risk factors to develop varicella pneumonia such as chronic lung diseases, previous or current smokers, third trimester of pregnancy and severity of the skin rash. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%